Evaluation of mixing effect and shear stress of different impeller combinations on nemadectin fermentation. (May 2020) - Wang, Zejian; Xue, Jiayun; Sun, Huijie; Zhao, Mingxia; Wang, Yonghong; Chu, Ju; Zhuang, Yingping
Graphical abstract: Highlights: Flow field characteristics were evaluated by laser particle image velocimetry system in nemadectin fermentation. Physiological parameters showed that shear stress seriously affect the mycelium growth and mycelial differentiation. The higher batch yield of nemadectin reached 1543.27 μg/mL under the radial-axial flow group. The radial-axial flow impeller combinations were conducive to nemadectin fermentation of Streptomyces cyaneogriseus . Abstract: Mass transfer and shear force have significant effects on nemadectin production by Streptomyces cyaneogriseus ssp . noncyanogenus . They are always the conflict-ridden problems in nemadectin fermentation process. In this study, the flow field characteristics under different impeller combinations were quantitatively evaluated in 5 L stirred-tank bioreactor through the laser particle image velocimetry (PIV) system. Results demonstrated that the radial-axial impeller combinations with the time average velocity at 0.38-0.54 Utip, the turbulent kinetic energy dissipation rate at 6.4–10.6 ε/N 3 D 2, and the shear stress rate was 40-150 s −1, were more conductive to cell growth, nemadectin biosynthesis, cell's activity, respiratory metabolism than other combinations. The highest nemadectin yield was evaluated up to 1543.3 ± 18.5 μg/mL, which was 31.68 % higher than that of the radial flow impeller combinations. This study provided the important guideline for the selection impeller combinations' on large-scale nemadectin production.